2007
DOI: 10.1080/00048670701449203
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Behavioural Assessment Tool for Cognition and Higher Function (BATCH) in Neuropsychiatric Patients

Abstract: BATCH scores correlated strongly with pencil-and-paper measures of cognitive function. BATCH provides clinicians with a means of assessing cognitive function through behavioural observation, thus enabling assessment of patients with behavioural disturbance or severe psychopathology. This tool has practical application for adult and aged clients across all observational mental health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A regression analysis showed the most significant determinant of the BATCH score was the cognitive function measured on NUCOG ( β = 0.400, P < 0.001) followed by functional status (Bristol Activities of Daily Living Scale (BADLS) β = −0.373, P < 0.01) and symptom status (Neuropsychiatric Inventory (NPI) β = −0.281, P < 0.01). The authors concluded BATCH can be a useful tool to assess cognitive function through observation in adults in any mental health setting 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A regression analysis showed the most significant determinant of the BATCH score was the cognitive function measured on NUCOG ( β = 0.400, P < 0.001) followed by functional status (Bristol Activities of Daily Living Scale (BADLS) β = −0.373, P < 0.01) and symptom status (Neuropsychiatric Inventory (NPI) β = −0.281, P < 0.01). The authors concluded BATCH can be a useful tool to assess cognitive function through observation in adults in any mental health setting 25 …”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded BATCH can be a useful tool to assess cognitive function through observation in adults in any mental health setting. 25 Another EF measure applied to psychiatric patients is the RNG task. This tool was previously described under the Factor Analysis section.…”
Section: Reliability and Validity Studiesmentioning
confidence: 99%
“…Nurses will be better equipped to tailor interventions to patients' cognitive abilities. Furthermore, behavioural observation within a clinical environment provides invaluable information regarding underlying cognitive function [25]. The value of observation of daily behaviour for assessing cognitive functioning was the reason for Miller et al to develop the BATCH (after we had finished our literature search).…”
Section: Discussionmentioning
confidence: 99%
“…The value of observation of daily behaviour for assessing cognitive functioning was the reason for Miller et al to develop the BATCH (after we had finished our literature search). This is an assessment tool to record observations of patients' daily functioning under subheading that reflect cognitive domains [25]. They were interested in an observation scale for patients in a psychiatric setting (mean age 50 years) who refuse or cannot undertake cognitive assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Physical disability did not correlate with the BATCH, as measured by the Barthel Index. Construct validity, internal consistency and correlation data were established and shown to be of high correlation (Miller et al .).…”
Section: Introductionmentioning
confidence: 99%